Covid-related change in consumer behavior in rural Pakistan - Riaz, Muhammad Usman; Chytková, Zuzana; Tahal, Radek, 1970-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The present study investigates the impact of COVID-19 on consumers' changing way of life and buying behavior based on their socio-economic backgrounds in rural areas of Pakistan. Unprecedented difficulties brought on by COVID-19 demand regional and international cooperation for their mitigation. Populations that are poor and marginalized are more susceptible to the pandemic's physical, social, and economic repercussions. Consumer behavior consists of 4 factors: Cultural, Social, Personal, and Psychological. In this study, we focus on the Psychological, Social, and Personal factors. The study was divided into a theory part and a findings/analysis part. The theory part discusses the factors affecting purchase decisions and consumer behavior during the pandemic. The findings and analysis part consists of general findings from the interviews collected and its subsequent analysis. A series of open-ended interviews were conducted with a total of 15 respondents belonging to rural areas of Pakistan in order to fully capitalize and analyze the impact of Covid-19 on consumers' affordability, lifestyle, health awareness, and how these effects influenced their buying behavior. The result of the study indicates that Personal, Psychological, Social and Cultural factors did have an effect on the consumer behavior of rural inhabitants. Furthermore, the study offers managers with valuable information on what kind of product substitutions might be feasible in the rural market during a pandemic.
Vedoucí práce: Zuzana Chytková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses